Discovery of 6-phenylimidazo[2, 1-b]thiazole derivatives as a new type of FLT3 inhibitors. Issue 20 (15th October 2015) - Lin, Xing-Dong; Yang, Hui-Wen; Ma, Shuang; Li, Wei-Wei; Zhang, Chun-Hui; Wang, Wen-Jing; Xiang, Rong; Li, Lin-Li; Yang, Sheng-Yong
Graphical abstract: Abstract: In this investigation, a series of 6-phenylimidazo[2, 1- b ]thiazole derivatives were synthesized. Structure–activity relationship (SAR) analysis of these compounds based on cellular assays led to the discovery of a number of compounds that showed potent activity against FLT3-dependent human acute myeloid leukemia (AML) cell line MV4-11, but very weak or no activity against FLT3-independent human cervical cancer cell line Hela. FLT3 kinase inhibition assays were then performed on the three most active compounds. Among these compounds, 6-(4-(3-(5-( tert -butyl)isoxazol- 3-yl)ureido)phenyl)- N -(3-(dimethylamino)propyl)imidazo[2, 1- b ]thiazole-3-carboxamide (19 ) exhibited the highest potency in both cellular (MV4-11, IC50 : 0.002 μM) and enzymatic (FLT3, IC50 : 0.022 μM) assays. Further in-depth in vitro anti-AML activity and mechanism of action studies were carried out on compound 19 .